China's policies for overcoming the crisis: old reflexes or strategy for a new reform miracle? - Doris Fischer (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
Since China's accession to the World Trade Organisation the world has witnessed the country's development with a mixture of admiration and fear. The economic growth rates have been extremely impressive, and cities like Beijing and Shanghai today do more and more resemble if not outperform other metropolis. At the same time, China's impact on global markets and on the environment, as well as a certain difficulty to under-stand the political logics of China, have created the idea of China being a challenge. One common misunderstanding in this context is to think of China as a monolith, centrally steered according to the will of the Chinese Communist Party. Though not totally wrong, this assumption easily neglects the fact that even at the level of the central government, discussions among politicians and experts prevail for each and every policy field, and published policies are generally compromises that still have to prove their effectiveness. Especially, in the years before the global financial crisis hit China, internal debates about suitable economic strategies for the country's long-term well-being proliferated. Since the crisis touched China, the government has initiated a number of policies in order to prevent a serious national economic downturn. The mix of policies initiated highlights conflicting positions within the government. External evaluations of China's reaction to the crisis should take the involved conflicts and compromises into account as they hint to different ideas concerning China's future, be it in terms of the role of the state, environmental policies or social equity.
Keywords: 330